2017
DOI: 10.3952/physics.v57i1.3453
|View full text |Cite
|
Sign up to set email alerts
|

AlAs as a Bi blocking barrier in GaAsBi multi-quantum wells: Structural analysis

Abstract: Crystallographic properties of AlAs barriers in GaAsBi-based multi-quantum well structures grown on GaAs substrates by molecular beam epitaxy (MBE) and migration-enhanced epitaxy (MEE) were studied. The quantum wells were grown at temperatures ranging from 160 to 350 °C. The width of GaAsBi quantum wells varied from 4 to 20 nm. The optimization of technological parameters for the growth of high crystalline quality AlAs barriers at low temperatures was performed. To explore the impact of high temperature treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Our group has demonstrated that AlAs layers prevent Bi out-diffusion from GaAsBi layers during an annealing procedure, and allows to adjust size of the Bi QDs that form in the quantum wells by varying the well width. [10] This work extends our initial studies by performing in-depth structural and chemical analysis of the system, as well as a statistical analysis of the Bi QD size distributions. Earlier HRTEM studies reported formation of Bi nanoparticles from 7.6 to 22 nm in size in thick GaAsBi layers.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…Our group has demonstrated that AlAs layers prevent Bi out-diffusion from GaAsBi layers during an annealing procedure, and allows to adjust size of the Bi QDs that form in the quantum wells by varying the well width. [10] This work extends our initial studies by performing in-depth structural and chemical analysis of the system, as well as a statistical analysis of the Bi QD size distributions. Earlier HRTEM studies reported formation of Bi nanoparticles from 7.6 to 22 nm in size in thick GaAsBi layers.…”
Section: Introductionmentioning
confidence: 67%
“…The latter process is accompanied by the formation Bi nanoparticles and reduction of Bi content in a surrounding GaAsBi layer. Our group has demonstrated that AlAs layers prevent Bi out‐diffusion from GaAsBi layers during an annealing procedure, and allows to adjust size of the Bi QDs that form in the quantum wells by varying the well width . This work extends our initial studies by performing in‐depth structural and chemical analysis of the system, as well as a statistical analysis of the Bi QD size distributions.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Then, the growth was interrupted and the substrate temperature was lowered for a growth of GaAsBi QWs and AlAs barriers. Migration-enhanced epitaxy (MEE) mode was used for AlAs deposition at the following growth sequence: one monolayer (ML) of Al, 5 s interruption for a migration of group III atoms, then a supply of 1 ML of As [ 14 , 15 ]. Finally, the MQW structure was covered by 5 nm-thick GaAs capping layer.…”
Section: Methodsmentioning
confidence: 99%